Influence of Social Media on Student Lifestyle in Metro City - Dewi Oktaviani (HM Publisher, 2020)
Social media is a medium that allows users to do social activities virtually with each other through the internet network. The use of social media is mainly used to show excessive self-existence that affects the perspective, lifestyle, and culture of a nation. Social media for IAIN Metro students is essential not only to get exciting information but also to become a lifestyle. This study aims to determine and describe the influence of social media on the lifestyle of IAIN Metro students. Researchers' research method is a type of field research (field research), qualitative descriptive. The data sources that researchers use are primary data sources and secondary data sources. Primary data sources were obtained from IAIN Metro students. Secondary data sources are obtained from books, the internet, and other literature. Methods of data collection, researchers used interviews, observation, and documentation. The researcher's data analysis method is data reduction, presenting data, and concluding data and verification. The results showed that IAIN Metro students used social media such as Instagram, WhatsApp, and Facebook. Social media has become a lifestyle for IAIN Metro students. The influence of social media on the lifestyle of IAIN Metro students has both positive and negative impacts. Judging from the aspect, the behavior of IAIN Metro students is included in impulsive buying because it is based on a sudden desire for a moment. Islam recommends a fair and balanced pattern of consumption and use of wealth, not being stingy and not being extravagant.